Structural Transformations of the Economy in the Pacific Region of Russia and Efficiency Trends - Baklanov, Peter Yakovlevich; Moshkov, Anatoly Vladimirovich (Economy of Regions, 2016)
Pacific Russia is considered as an aqua-territorial macro-region entering the Far Eastern Federal Okrug and its adjacent water area within a 200-mile sea economic zone. 7he macro-region has the richest nature-resource potential of a dry land and the sea, the possibilities to use the sea transport for communications of Russia and Europe with the countries of the Asian-Pacific region. In Pacific Russia, two latitudinal zones are allocated: the northern and southern ones, consisting of the territories of the Far Eastern Federal Okrug of Russia. Combinations of activities by the subjects and by the latitudinal zones are considered as the territorial structures of economy. 7he distinctions of these latitudinal zones by their socio-economic potential and the level of development are shown. By the changes of homogeneous activities in the subjects and their ratios, measured in the shares of the added cost, the assessment of the structural transformation of economy was carried out in the latitudinal zones from 2004 to 2013. The tendencies of the transformation of the territorial structures of economy were revealed in the latitudinal zones. The greatest changes of the structures of economy occurred in the northern zone for this period. In the southern zone, the structural transformations of economy were a little less, except for Sakhalin. In this case, in both latitudinal zones, a share of processing manufactures reduced and that of the extracting industries increased. The generalized assessment of the changes in social and economic efficiency (by increased personal income, labor productivity, profits) in correlation with the structural changes in the economy of the regions of Pacific Russia has been made. The authors note that an important premise for building a sufficiently sustainable system of interregional division of labor in Pacific Russia is the location of extractive industries and initial stages of the manufacturing industry activities in the northern zone, while the major manufacturing industries and interregional transport and logistics services are located in the southern zone. The article is intended for the experts and the students, interested in the problems of the development of the eastern regions of Russia.